2024 EU elections and French politics: rise of populism, eurocentrism, and inter-institutional dynamics - Kahil, Angela (Frontiers in Political Science, 2025)
IntroductionThis study investigates the impact of the 2024 European Union (EU) elections on France, focusing on the interplay between EU institutions, national governments, parliaments, and political parties within the context of Eurocentrism. It examines how EU elections influence national policymaking and political competition in France, particularly in light of the rise of populist parties within the EU Parliament.MethodsThe research employs a multi-level qualitative and comparative approach, analyzing recent EU electoral outcomes and their consequences for French political behavior. Qualitative methods, including case studies and discourse analysis, are used to assess the dynamics between French political actors and EU institutions, as well as the shaping of domestic political agendas and Eurocentric narratives.ResultsThe findings reveal that the 2024 EU elections significantly influenced French political dynamics, particularly through the growing presence of populist parties in the EU Parliament. These elections shaped national policymaking and political competition, reinforcing the Reif and Schmitt 1980’s concept of EU elections as “second-order elections”. The study highlights the dual role of EU elections in reflecting national political trends while driving supranational policy agendas. The results underscore the evolving relationship between national and supranational governance, emphasizing the challenges posed by populism and Euroscepticism to European integration.DiscussionThe study contributes to the understanding of inter-institutional relations and their impact on policymaking, offering insights for scholars and policymakers concerned with the future of the EU and its implications for member states like France. This research provides valuable perspectives on the 2024 EU elections and their consequences for France, highlighting the complexities of European integration in an era of rising populism. It calls for further exploration of the long-term effects of these dynamics on EU governance.